Sigma-1 Receptor Changes Observed in Chronic Pelvic Pain Patients: A Pilot PET/MRI Study - Yoon, Daehyun; Fast, Angela M.; Cipriano, Peter; Shen, Bin; Castillo, Jessa B.; McCurdy, Christopher R.; Mari Aparici, Carina; Lum, Deirdre; Biswal, Sandip (Frontiers in Pain Research, 2021)
Introduction: Chronic pelvic pain is a highly prevalent pain condition among women, but identifying the exact cause of pelvic pain remains a significant diagnostic challenge. In this study, we explored a new diagnostic approach with PET/MRI of the sigma-1 receptor, a chaperone protein modulating ion channels for activating nociceptive processes. Methods: Our approach is implemented by a simultaneous PET/MRI scan with a novel radioligand, [18F]FTC-146, which is highly specific to the sigma-1 receptor. We recruited 5 chronic pelvic pain patients and 5 healthy volunteers and compared our PET/MRI findings between these two groups. Results: All five patients showed abnormally increased radioligand uptake on PET compared to healthy controls at various organs, including the uterus, vagina, pelvic bowel, gluteus maximus muscle, and liver. However, on MRI, only 2 patients showed abnormalities that could be potentially associated with the pain symptoms. For a subset of patients, the association of pain and the abnormally increased radioligand uptake was further validated by successful pain relief outcomes following surgery or trigger point injections to the identified abnormalities. Conclusion: In this preliminary study, sigma-1 receptor PET/MRI demonstrated potential for identifying abnormalities associated with chronic pelvic pain. Future studies will need to correlate samples with imaging findings to further validate the correlation between S1R distribution and pathologies of chronic pelvic pain. Trial registration: The clinical trial registration date is June 2, 2018, and the registration number of the study is NCT03195270 (https://clinicaltrials.gov/ct2/show/NCT03556137).